Factors associated with feeding adequacy and relationships between feeding adequacy and 60-day mortality in the intensive care unit in a Malaysian hospital - Lee, Zheng Yii (2017)
Guidelines recommended to feed critically ill patients adequately to ensure optimum clinical outcomes. Nevertheless, underfeeding is commonly reported, but the factors associated with feeding adequacy are not clear. The contribution of feeding adequacy on clinical outcomes are also becoming controversial recently. This study was conducted to (1) investigate factors associated with feeding adequacy and (2) to determine the relationship between feeding adequacy and 60-day mortality among critically ill patients in the intensive care unit of Hospital Serdang. This study employed a prospective observational design. Adult patients (≥18 years old) who were mechanically ventilated within 48 hours of ICU admission and stayed in the ICU for at least three days were included. Demographic characteristics and nutrition risk (modified-NUTRIC) score were collected on day 1.Feeding characteristics were collected for a maximum of 12 evaluable nutrition days or until patients died or discharged. Clinical outcomes including the length of stay, duration of mechanical ventilation and mortality status were collected in hospital at day 60. Data were collected on a total of 154 patients with 1406 evaluable nutrition days. The mean 12-day energy and protein adequacy were 64.48 ± 21.57% and 56.42 ± 20.68%, respectively. The top three categories of reasons for feeding interruption were due to procedures, potentially avoidable reasons and illness-related intolerances. Patient were divided into high (received ≥2/3 of prescribed) or low (received <2/3 of prescribed) energy and protein adequacy. Factors that significantly associated with higher energy adequacy were earlier feeding commencement, less enteral nutrition (EN) interruption, dietitian visits and the longer number of nutrition days. Factors that significantly associated with higher protein adequacy were earlier feeding commencement, less EN interruption, longer number of nutrition day, Chinese race and non-diabetic. At day-60, 44.8% of the patients died. Trend towards an increased in 60-day mortality was demonstrated for high energy and high protein adequacy after adjusted for potential confounders (Adjusted Odds Ratio: 1.99 and 1.93; p=0.089 and 0.116, respectively). When stratified by nutritional risk classification, patients with low nutritional risk (NUTRIC ≤5) had increased 60-day mortality if they were in the high energy and high protein group but the relationship was not observed among patients with high nutritional risk (NUTRIC >5). In conclusion, almost half of the energy and protein prescribed were not met. Independent predictors for both high energy and protein adequacy were earlier feeding commencement, less EN interruption and the longer number of nutrition days. However, energy and protein adequacy of ≥2/3 of prescribed increased 60-day mortality among patients with low nutritional risk. Therefore, it is suggested to screen all patient admitted into the ICU for nutrition risk status.